Home Care Holistic on the Change of Anxiety and Depression for the Patient with Stroke Ischemic - Luluk Widarti; Krisnawati Krisnawati (Universitas Airlangga, 2012)
Introduction: Stroke is the main cause of long-term disability. It was reported that one third out of stroke survivors showed dementia in three months after stroke. Stroke patients need medication and palliative caring so that home-care is highly recommended. In Indonesia, home-care nursing for ischemic stroke has not yet been optimally applied in caring patient with stroke. The objective of thestudy was to examine the effect of home care holistic nursing on the change of anxiety and depression for the patient with stroke ischemic.Method: An experimental research with quasy experimental speciﬁcally nonrandomized pre-post test control group design was applied in this study. The study was conducted in Surabaya by selecting ischemic stroke patients after being hospitalized at